ANALISIS PROFITABILITAS PATA PT. PEGADAIAN (PERSERO) KANWIL V MANADO - PONTOH, NATALIA; PELLENG, FRENDY A. O.; MUKUAN, DANNY D. S. (Sam Ratulangi University, 2016)
Absrtact. This research has been conducted in order to collect information on the financial statements from 2014 until 2015 that the balance sheet and income statement at PT. Pawnshop (Persero) Regional Office V Manado in Manado in July 2016. This study uses the theoretical basis of the theory of financial management regarding profitability ratio analysis of the financial statements, analytical tools used in this study Gross Profit Margin, Net Profit Margin, Return on Investment and return on Equity. Based on the analysis shows that the Gross Profit Margin PT. Pawnshop (Persero) Regional Office V Manado in Manado decreased from 2014 to 2015, judging from the Net Profit Margin for three years beginning in 2014 until 2015 has decreased. Then Return on Equity and Return On Investment achieved during the year 2014 to 2015, the results showed the same percentage, which decreased in 2015. The results of this study indicate that the ratio of profitability in the financial statements. Pawnshop (Persero) Regional Office V Manado in Manado yet stable and efficient enough to run the company's daily operations.Based on the formulation of the problem of the study